Out-of-home care and diagnosed mental and behavioral disorders among youth with and without prenatal substance exposure – A longitudinal register-based cohort study - Koponen Anne M.; Nissinen Niina-Maria; Gissler Mika; Kahila Hanna; Autti-Rämö Ilona; Sarkola Taisto (Elsevier Ltd, 2022)
A majority of youths with prenatal substance exposure (PSE) have experienced out-of-home care (OHC), but there is a lack of studies on its association with mental health in adolescence and adulthood. The main aim of this retrospective longitudinal cohort study was to explore whether type of OHC (family/institutional) and number of OHC placements are associated with mental and behavioral disorders among youth with PSE (n = 393) and unexposed controls (n = 147) after controlling for the effect of important confounding factors. Before these analyses, characteristics of OHC and factors associated with the age at entry to care were analyzed separately in both groups. Data from hospital medical records and nine registers were merged and analyzed using descriptive statistics, Pearson correlations and multivariate Cox regression models. Exposed youths entered OHC earlier in life, and the lifetime duration of OHC was longer with more placements and a higher proportion of family-type OHC. Despite these differences in OHC history, a high number of placements was associated with behavioral and emotional disorders with onset in childhood and adolescence (International Statistical Classification of Diseases ICD-10, F90-F98) among both the exposed and controls. Among the exposed, the number of placements and institutional care were also associated with later appearing mental and behavioral disorders (F10-F69). The results suggest that interventions to support placement stability and favor family-type care could be beneficial in the promotion of mental health among children and youth entering OHC.